Review Ergogenic Effect of Long Jack, Eurycoma Longifolia - Khanijou, Thasanee; Jiraungkoorskul, Wannee (Pharmacognosy Reviews)
Eurycoma longifolia (family: Simaroubaceae) is commonly distributed in the Southeast Asia and Indo‑China. In particular, the aqueous extract and decoction of its root are a well‑known folk medicine which enhances sexuality, fertility, and antiaging. Furthermore, it has been shown to possess anti‑inflammatory, antimalarial, antimicrobial, and antioxidant properties. Its common phytochemical components include alkaloids, flavonoids, phenolics, saponins, tannins, and triterpenes. This plant is rich in various quassinoids including eurycolactone, eurycomalactone, eurycomanol, eurycomanone, and eurycomaoside all of which has been reported to contribute to its remedial properties including increased muscle strength, endurance in cycling time, and reduced anxiety and stress. Based on established literature on the health benefits of E. longifolia, this review article has attempted to compile E. longifolia to be one of the choices of ergogenic plants.
Keywords: Ergogenic aids; Eurycoma longifolia; exercise; herb; plant; traditional medicine